Knowledge of Meaning, Conscious and Unconscious - Steven Gross (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
This paper motivates two bases for ascribing propositional semantic knowledge (or something knowledge-like): first, because it's necessary to rationalize linguistic action; and, second, because it's part of an empirical theory that would explain various aspects of linguistic behavior. The semantic knowledge ascribed on these two bases seems to differ in content, epistemic status, and cognitive role. This raises the question: how are they related, if at all? The bulk of the paper addresses this question. It distinguishes a variety of answers and their varying philosophical and empirical commitments.